Cervantes e la novella - Zamora Calvo, María Jesús (Rassegna Iberistica, 2014)
In addition to the literary value inherent in Cervantes’s last work Los trabajos de Persiles y Segismunda, the short stories intercalated in the novel that constitute our corpus are culturally complex and fascinating. The narration is marked by traditional components signaling both oral and written transmission. Therein lies the purpose of this study, which is to examine the characteristics that mark and define the stories from both of these traditions that have been inserted throughout the work of Persiles.